BURUNG ELANG DALAM KARYA SENI LUKIS KONTEMPORER - Alga Surista Pura, Drs. Erfahmi, M.Sn., Drs. Yusron Wikarya, M.Pd. (Serupa The Journal of Art Education, 2017)
The purpose of this article is to visualize the unique behavior of eagle's life as a guide and motivation in human life through contemporary painting. Eagle as an ideas in this article as a medium of information to the public to be able to admire eagles so eager to maintain their habitat. This method in realizing ideas of art include: preparation, elaboration stage, synthesis, concept realization and completion. This work describes the behavior of eagles in the wild. As a result of the discussion and stages creation of ten (10) works that gives more motivation, information, as well as learning to make human character in life and theirs life.Kata kunci: Burung Elang, Seni Lukis Kontemporer